AB0952 Intra-articular low molecular weight hyaluronate reduces platelet influx and matrix metalloproteinase-2 levels in synovial fluid of patients with knee osteoarthritis. (23rd January 2014) - Alunno, A.; Luccioli, F.; Falcinelli, E.; Santoboni, G.; Momi, S.; Bartoloni, E.; Petito, E.; Bistoni, O.; Mirabelli, G.; Gresele, P.; Gerli, R.
Abstract : Background: Matrix metalloproteinaeses (MMPs) are a large family of zinc-dependent endoproteinases that cleave several components of the extracellular matrix (ECM) and that are tightly regulated by tissue type MMP inhibitors (TIMPs). The joint cartilage and bone degradation that occurs in osteoarthritis (OA) is in part the consequence of an imbalance between MMPs and TIMPs. MMPs are released by several cell types, including platelets that have been recently shown to participate in the inflammatory processes of arthritis. Among platelet-derived MMPs, MMP-2 is of particular potential relevance for OA. Hyaluronic acid (HA), a core component of ECM, is a critical constituent of normal synovial fluid and plays a pivotal role in joint homeostasis. In clinical practice, intra-articular injection of low molecular weight HA (LMW-HA) has been used as visco-supplementation for knee OA and its therapeutic efficacy has been verified in a number of studies. Objectives: Aim of the present study was to investigate the effect of a short treatment with LMW-HA on platelet derived MMP-2 in the synovial fluid and possible correlations with clinical response. Methods: Nineteen patients with knee OA were enrolled. Synovial fluid (SF) samples were collected before (T0) and after 5 weeks of intra-articular LMW-HA (T1) (4 injections, one week apart). Western Ontario and McMaster Universities Arthritis Index (WOMAC) and global pain visual analogic scale (VAS) were also collected at both time-points. MMP-2 measurement in SF was performed by zymography. SF inflammatory cell count was performed optically, by a Burker Chamber, while platelets were counted by flow cytometry. Results: SF MMP-2 levels, platelet activation, platelet, monocyte and eosinophil numbers, were all significantly reduced at T1, while lymphocyte and synoviocyte number was not affected. A direct correlation between platelet number and MMP-2 concentration in SF was observed at both time-points (p<0.01). Patients achieved a good clinical response with reduction of all WOMAC items and VAS pain (all p<0.0001) Conclusions: The results of the present study show that LMW-HA decreases the intra-articular amount of platelets and of MMP-2. These data suggest a potential role for platelets in cartilage degradation in OA, possibly by the local release of MMP-2. LMW-HA, besides its symptomatic benefit, may play a role in slowing down cartilage degradation and eventually OA progression. References: Wang CT et al. Osteoarthritis and Cartilage 2006;14:1237. Falcinelli E et al. Br J Haematol 2007;138:221. Disclosure of Interest: None Declared